CASE STUDY OF SECOND LANGUAGE ACQUISITION OF AN EIGHT YEAR OLD CHILD - Oktaviana, Eflin; Purwanti, Indah Tri; Eliwarti, Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research discusses a case study of second language acquisition of an 8 year old child in Duri Riau. A qualitative approach was applied to this descriptive study. The data were gathered through a qualitative method by observing and recording. The researcher recorded, transcribed, analyzed, and classified the gathered data to determine the types of sentences and factors influencing in acquiring the foreign language . The findings showed that the research participant was able to produce some types of sentences, namely declarative sentences, interrogative sentences, imperative, and exclamatory sentences. The types of sentences were produced in conjunction with their communicative purposes. Besides, it was also revealed that the participant was able to produce sentences using various tenses: present tense and past tense both in positive and negative forms. In addition, the participant sometimes did code mixing between English to Indonesian and Indonesian to English when talking with people who used Indonesian. To find out the factors affecting the acquisition of the foreign language, the researcher analyzed the data using the theory of Lightbown and Spada (2006) which is relevant to this study. From the behaviorist side, it was revealed that cartoon movies, YouTube, books, and English kids’ songs were the factors that affected the participant in acquiring L2 . Moreover, the role of the caregiver influenced the development of the participant’s foreign second language acquisition. However, the role of the caregiver in this study was only as a facilitator that was to help the participant acquire the foreign language, and the person who played the role of the caregiver was the mother of the research participant.Key Words: Language acquisition, Second language acquisition, Children eight years old